Regulations and instructions in the Polish Oriental School in Istanbul from 1766, 1772 and 1778 - Bajer, Jakub (Instytut Historii Nauki im. Ludwika i Aleksandra Birkenmajerów Polskiej Akademii Nauk, 2021)
The article aims to present the content of three rulebooks drawn up in French for students and teachers of the Polish Oriental School in Istanbul in 1766, 1772 and 1778. These materials come from the Princes Czartoryski Library in Kraków and the Popiel Collection in the Central Archives of Historical Records in Warsaw. The first instruction was drawn up in the year of the establishment of the Polish Oriental School [Jeunes de langues] on the Bosphorus, namely in 1766. It was written by Tomasz Aleksandrowicz and Karol Boscamp-Lasopolski in accordance with the recommendations received earlier by these two diplomats from King Stanisław II August. Another regulation was created in His Majesty’s Cabinet six years later, in 1772. Its author was Jacek Bartłomiej Ogrodzki, a close associate of the monarch. The last regulation known from literature was created on the occasion of Karol Boscamp-Lasopolski’s legation to Turkey in 1778. The changes in the recommendations for students and teachers over the course of 12 years show the obstacles and difficulties faced by the creators of the first Polish school for dragomans.
Keywords: Polish Oriental School; history of education; Polish–Turkish relations